Taxation of Professional Team Sport Athletes in the Czech Republic - Radvan, Michal; Neckář, Jan (Public Governance, Administration and Finances Law Review, 2016)
The career of a professional athlete is unique when compared to other professions. Not purely the role and nature of the position (such as whether they are individual or team players), but also from the factual, legal, and especially tax perspectives. And since a professional athlete’s income is subject to taxation, it is necessary that their activity is accurately determined for appropriate tax assessment. The main purpose of this article is to examine the taxation of income on professional athletes in team sports. Our study is based on case law determined by the Czech Republic’s Supreme Administrative Court (hereinafter ‘Supreme Administrative Court’), which determined that it is necessary to tax the activities of team players as income from self-employment. The existing scientific literature on this subject in the Czech Republic is not particularly relevant, as it is mostly descriptive. International scientific literature is more abundant and comprehensive, such as noted publications by Tetłak, Simpson, and Taxation of Artistes and Sportsmen in International Tax Law, edited by Loukota and Stefaner.